DEVELOPING FISHING VILLAGE TOURISM IN LANG CO - HUE WITH REFERENCE TO FISHING VILLAGE TOURISM IN ZADAR - CROATIA - Dinh Thien Phuong; Ho Thi Dieu Hien (HUIT Journal of Science, 2025)
Lang Co Bay is a beautiful landscape of Hue city with rich tourism resources. However, the tourist attraction of this place is not yet commensurate with its potential. Sharing the same natural terrain as Lang Co Bay, Zadar Bay has attracted 5 times more tourists than Lang Co Bay through fishing village tourism. Through comparative study, this article will focus on analyzing the limitations in planning and organizing tourism in Lang Co compared to tourism in Zadar in the direction of developing fishing village tourism - a part of rural tourism. In addition, through an overview of some fishing village models in Asia, the article will also present some measures to develop fishing village tourism in Lang Co in the direction of ensuring economic, environmental and social sustainability.